2014
DOI: 10.1007/s00421-013-2813-6
|View full text |Cite
|
Sign up to set email alerts
|

The order effect of combined endurance and strength loadings on force and hormone responses: effects of prolonged training

Abstract: Running title: Training-induced responses to combined loadingsThe funding for this study has been provided by the Finnish Ministry of Education and Culture. 2 ABSTRACTPurpose: To examine acute responses and recovery of force and serum hormones to combined endurance and strength loadings utilizing different orders of exercises before and after training. Methods:Physically active men were matched to an order sequence of endurance+strength (E+S, n=12) or strength+endurance (S+E, n=17). The subjects performed one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
1
14
0
1
Order By: Relevance
“…As all participants in the present study had 2 years of strength training history and as such were considered resistance trained it is unlikely that the training status of accounts for the similar testosterone responses reported here. Both Schumann et al (2014) and Taipale and Häkkinen (2013) reported no order effect on testosterone responses, the authors also observed no significant increases in testosterone in either condition (ST-END or END-ST). As previously discussed programme variables such as load, set/rep scheme and rest periods influences the endocrine responses to strength loading (Hakkinen & Pakarinen, 1993 and Taipale and Häkkinen (2013) both incorporated aspects of strength and power loadings (as opposed to hypertrophy), this may explain the similar responses of testosterone to both sequences of strength and endurance loading and lack of significant elevations in testosterone.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…As all participants in the present study had 2 years of strength training history and as such were considered resistance trained it is unlikely that the training status of accounts for the similar testosterone responses reported here. Both Schumann et al (2014) and Taipale and Häkkinen (2013) reported no order effect on testosterone responses, the authors also observed no significant increases in testosterone in either condition (ST-END or END-ST). As previously discussed programme variables such as load, set/rep scheme and rest periods influences the endocrine responses to strength loading (Hakkinen & Pakarinen, 1993 and Taipale and Häkkinen (2013) both incorporated aspects of strength and power loadings (as opposed to hypertrophy), this may explain the similar responses of testosterone to both sequences of strength and endurance loading and lack of significant elevations in testosterone.…”
Section: Discussionmentioning
confidence: 90%
“…Previous research has demonstrated strength development is greater when strength precedes endurance training rather than vice versa (Cadore, Izquierdo, Alberton, et al, 2012;Collins & Snow, 1993). In contrast, others have reported no differences in strength development following either sequence of strength and endurance training (Chtara et al, 2008;Davitt, Pellegrino, Schanzer, Tjionas, & Arent, 2014;Schumann et al, 2014;Rosa et al, 2015). The variances in findings are likely attributable to the differing strength training protocols employed, as it is widely accepted that the set x rep scheme and load imposed influences the responses of primary hormones (Spiering et al, 2008).…”
Section: Introductionmentioning
confidence: 96%
“…Of note, the available studies on the acute effects of AE on measures of muscle strength and power have shown inconsistent findings. More specifically, while some studies reported attenuated strength and power outcomes [19][20][21], others showed post-activation performance enhancement (PAPE) most likely triggered by the previous AE [22][23][24]. For example, Lepers et al [25] studied the acute effects of two different cycling modalities (i.e., constant and variable power output) on measures of muscle strength in trained male triathletes aged 33 years.…”
Section: Introductionmentioning
confidence: 99%
“…За зміною вмісту гормонів можна судити про адаптацію організму до фізичних навантажень, інтенсивність регульованих ними метаболічних процесів, розвиток процесів стомлення, що дозволить визначити основні параметри навантажень при плануванні програм підготовки [10,11,18,21,24]. Відомо, що вміст гормонів у крові залежить від багатьох факторів, у тому числі: статі, циркадних ритмів, харчування, нав колишнього середовища (температура, вологість), емоційного стану, потужності й тривалості виконуваних навантажень, а також від рівня тренованості спортсмена [12,22,23].…”
unclassified